How searcher shoots grow and branch in mature liana mats: the case of Merremia boisiana - Kuang, Qiyu; Su, Shiying; Hu, Liang (Frontiers in Plant Science, 2024)
The proliferation of vigorous lianas usually forms liana canopies over the crowns of host trees and liana mats on the ground of open areas or large forest gaps. While research on liana canopies has increased significantly in recent decades, our understanding of liana mats remains limited. Merremia boisiana (Convolvulaceae), a fast-growing liana, forms mature liana mats that can persist for decades, characterized by numerous upright searcher shoots that extend from the liana mats in search of supports. However, the reasons behind the proliferation of these searchers, as well as their growth and branching patterns in mature liana mats that lack support, are not well understood. We hypothesize that searchers are an inevitable phase in the growth rhythm of M. boisiana within these mature liana mats. We tested our hypothesis by tracking the lifespan and status of M. boisiana searchers during the early, middle, and late periods of the year. Our findings reveal the following: (1) M. boisiana searchers exhibit apical dominance and have a short lifespan; over 95% of searchers lost their terminal buds within two months during the early period, while it took only one month during the middle and late periods.(2) The original lateral buds of the searchers also have a limited lifespan, yet the nodes can sprout new lateral buds after the loss of their originals. ( 3) With the withering of terminal buds, the total number of lateral shoots decreased, while the quantity of long lateral shoots (≥ 50 cm) and their elongation rates increased. (4) Each surviving segment of a searcher typically develops one or two long lateral shoots, none of which grow into searchers. We conclude that the shoots of M. boisiana in mature liana mats periodically alternate between searchers and stolons, collectively forming a zigzag branching system. The high rate of lateral bud resprouting may facilitate the rapid recovery of mature liana mats early in the year, while the reduced lifespan of searchers and limited number of long lateral shoots represent effective strategies for M. boisiana, balancing the investment and risk associated with foraging in mature liana mats.